Reconstruction of Ranking System Based on Maslow and Al-Ghazali's Motivation Theory in Elementary School - Muhamad Parhan; Andini Fitriani; Anggi Nur Pramesti; Cucu Cahyati (Universitas Pendidikan Indonesia (UPI), 2020)
Start from Abraham Maslow's motivational theory which states that humans need appreciation, this research is attempt by the researchers in studying the ranking system in elementary schools. The competition system is known to grow the education system in a country like South Korea and Japan which have high literacy levels. This competition system is also applied in Indonesia, with giving a ranking which can foster a competitive spirit and high motivation. However, many students feel anxious when their ranking decreases. Therefore, Al-Ghazali's Motivation Theory can be a solution for student anxiety. This research uses mix methods, namely quantitative methods in the form of data analysis of questionnaire results and qualitative methods in the form of questionnaires, literature studies, and simple interviews conducted to several different sources. Through this research we expected that the competition system in elementary schools can become a healthy competition system both physically and spiritually.